3-Year Outcomes of XEN Implant Compared With Trabeculectomy, With or Without Phacoemulsification for Open Angle Glaucoma. Issue 10 (1st August 2022) - Marcos-Parra, María Teresa; Mendoza-Moreira, Angi Lizbeth; Moreno-Castro, Lucía; Mateos-Marcos, Carlos; Salinas-López, Javier Alejandro; Figuerola-García, María Belén; González-Alonso, Ángela; Pérez-Santonja, Juan José
Abstract : Précis: Trabeculectomy (TRAB) surgery reduces the intraocular pressure (IOP) more than the XEN45 implant over 3 years. There is no difference in the number of antiglaucoma medications between the 2 procedures. The decision to perform either TRAB or XEN45 implantation must be evaluated on a case-by-case basis, taking into account the high rate of needling of the XEN45. Purpose: The aim of this study was to compare the differences between the efficacy and safety of the XEN45 implant and TRAB, either alone or in combination with phacoemulsification (PHACO), in patients with open angle glaucoma (OAG) at 36 months. Methods: A retrospective, single-center and comparative study conducted on OAG patients who underwent XEN45 implantation or TRAB from 2016 to 2018. Patients were divided into 4 groups: group 1 (XEN45 alone), group 2 (XEN45+PHACO), group 3 (TRAB alone), and group 4 (TRAB+PHACO). For statistical purposes, groups 1 and 2 were combined (XEN45 implant), whereas groups 3 and 4 were also combined (TRAB surgery). IOP, number of glaucoma medications, and adverse events were evaluated. The main outcome measure was the reduction in IOP at 36 months postoperatively. Results: One hundred thirty-four patients (134 eyes; 63 XEN45 and 71 TRAB) were included. The mean (95% confidence interval) IOP reduction at the end of the study follow-up was −6.3 (−11.0 to −1.6 mm Hg, P =0.025, XEN45 alone), −8.9 (−11.0 to −6.8 mm Hg, P <0.001, TRAB alone), −2.5 (−4.5 to −0.4 mm Hg, P =0.019, XEN45+PHACO), and −5.6 (−7.7 to −3.4 mm Hg, P <0.001, TRAB±PHACO). The proportion of patients achieving an IOP≥6 and ≤16 mm Hg without treatment at the end of the 36-month follow-up were 50.8% (32/63) in the XEN45 implant and 49.3% (35/71) in the TRAB surgery group, P =0.863. The mean number of glaucoma medications was significantly reduced in all the study groups. The needling rate was 19% in XEN45 versus 5.6% in the TRAB group ( P =0.030), and 2.81% and 36.6% of eyes in the TRAB group presented anterior chamber flattening and hyphema, respectively. Conclusions: TRAB surgery lowered IOP significantly more than XEN45 implant with or without phacoemulsification over 3 years and had a significantly lower need for additional needling surgery. Both procedures reduced glaucoma medications to a similar rate. These findings are relevant to the informed consent process and patient decisions for one procedure over the other.